2019
DOI: 10.1186/s12872-019-1255-4
|View full text |Cite
|
Sign up to set email alerts
|

Towards standardized postprocessing of global longitudinal strain by feature tracking – OptiStrain CMR-FT study

Abstract: BackgroundLeft ventricular global longitudinal strain (GLS) with cardiovascular magnetic resonance (CMR) is an important prognostic biomarker. Its everyday clinical use is limited due to methodological and postprocessing diversity among the users and vendors. Standardization of postprocessing approaches may reduce the random operator-dependent variability, allowing for comparability of measurements despite the systematic vendor-related differences.MethodsWe investigated the random component of variability in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…This is often cited as the main reason why clinical routine implementation is lagging. Training and standardisation may overcome the bias introduced by inconsistent software application and will probably lead to reduced observer‐induced variability 18,36 . Despite high consistency and correlation among vendors, differences in absolute agreement and absolute strain values suggest a requirement for software‐specific reference values and furthermore a need for further standardisation to allow easy clinical routine implementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is often cited as the main reason why clinical routine implementation is lagging. Training and standardisation may overcome the bias introduced by inconsistent software application and will probably lead to reduced observer‐induced variability 18,36 . Despite high consistency and correlation among vendors, differences in absolute agreement and absolute strain values suggest a requirement for software‐specific reference values and furthermore a need for further standardisation to allow easy clinical routine implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Training and standardisation may overcome the bias introduced by inconsistent software application and will probably lead to reduced observer-induced variability. 18,36 Despite high consistency and correlation among vendors, differences in absolute agreement and absolute strain values suggest a requirement for software-specific reference values and furthermore a need for further standardisation to allow easy clinical routine implementation. Beyond limited agreement within FT-derived deformation assessment, the current data demonstrate distinct deviations for different approaches applied to evaluate myocardial deformation.…”
Section: Agreementmentioning
confidence: 99%
“…Heinke et al (17) described a post-processing standardisation of deriving CMR-FT GLS in which assessors evaluated the quality of contour placement following manual delineation and performed adjustments as necessary based on evidence of poor tracking. This approach was shown to improve intra-and inter-observer agreement when comparing pre-and post-standardisation data.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, strain analysis was performed using only a single software. The literature shows that inter-vendor reproducibility is a limiting factor for routine implementation of CMR-FT in clinical practice, with a recent study by Heinke et al highlighting the need for standardised postprocessing of GLS measurements in reducing variability [ 25 ]. Although this study focusses on global strain, the issue of intervendor variability has also been reported in measuring multi-layer segmental strain [ 26 ].…”
Section: Discussionmentioning
confidence: 99%